2014
DOI: 10.3109/09537104.2014.931569
|View full text |Cite
|
Sign up to set email alerts
|

Effect of hemodialysis on platelet function in end-stage renal disease Egyptian patients using in vitro closure time test (PFA-100 analyzer)

Abstract: In patients with end-stage renal disease (ESRD), hemorrhagic complications are commonly encountered due to abnormalities in primary hemostasis, in particular, platelet (PLT) dysfunction and impaired PLT-vessel wall interaction. The pathogenesis of altered PLT function is considered multifactorial. Dialysis procedures had a favorable impact on bleeding complications in uremic patients. We aimed to evaluate the effect of hemodialysis on PLT function in patients with ESRD on a regular hemodialysis program. This s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
13
2
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 18 publications
2
13
2
1
Order By: Relevance
“…37,38 In this present study platelet count and other platelet indices were improved, similar findings seen in other studies. 11,28,29 In our study, there was decrease in haemoglobin and haematocrit values in patients before haemodialysis session compared to controls. These values were increased in patients after haemodialysis.…”
Section: Discussionsupporting
confidence: 44%
“…37,38 In this present study platelet count and other platelet indices were improved, similar findings seen in other studies. 11,28,29 In our study, there was decrease in haemoglobin and haematocrit values in patients before haemodialysis session compared to controls. These values were increased in patients after haemodialysis.…”
Section: Discussionsupporting
confidence: 44%
“…10 The presence of uremic substances like urea, guanidine succinate, phenol, parathyroid hormone, and tryptophan products inhibits platelet function. 11 Parathyroid hormone was not significantly different between the two RRT groups (p ¼ 0.88). However, urea significantly differed between the two groups (p ¼ 0.003) and was therefore added into the hierarchical multiple linear regression model.…”
Section: Discussionmentioning
confidence: 85%
“…90% of the patients had a predialysis CT prolongation that returned to normal ranges in 22% of those patients after the HD session. 11 Besides that, Knehtl et al 20 compared PFA-100 of chronic HD patients before and after HD sessions with five different anticoagulation methods (full-dose unfractionated heparin, low-molecular-weight heparin, low-dose heparin, regional citrate, and heparin-free) and did not observe any improvements between pre-and postdialysis values and any differences between different types of anticoagulation methods. 18 Concerning our HD patients, all received full-dose heparin (5,000 I.U./session) during the HD session but it is known that heparin does not affect CT. 19 PD may be more effective in normalizing primary hemostasis caused by uremia than HD due to relatively higher hematocrit levels, an absence of platelet activation by artifi-cial surfaces, and improved clearance of middle molecules.…”
Section: Discussionmentioning
confidence: 99%
“…Both mean PLT volume and PLT distribution width were reported to be decreased in patients with mild cognitive impairment and Alzheimer’s disease 39 . In addition, PLTs were previously shown to be exhausted after hemodialysis because of repeated hemodialysis stimulation and recurrent release of PLT degranulation products 40 . The results of the current study showed that blood PLT counts were significantly decreased in hemodialysis patients with MCD than that of healthy control individuals and hemodialysis patients with NCF.…”
Section: Discussionmentioning
confidence: 99%